Transmisi Peradaban Islam ke Dunia Barat: Jalur, Kontribusi, dan Dampaknya terhadap Renaisans Eropa - Rayyahun, Annisa; Sukmana, Ahyana Syahila; Widianti, Anyta; Hasaruddin; Harisa, Rahmawati (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This study aims to explore the contributions of Islamic civilization to the development of the Western world, particularly between the 8th and 15th centuries CE. Using a historical-analytical approach and literature review, the research reveals how knowledge, philosophy, art, and technology from the Islamic world were transmitted to Europe through key channels such as Al-Andalus, trade routes, the Crusades, translation movements, and Islamic educational centers. The findings show that Islamic contributions played a pivotal role in laying the foundation for the Renaissance and the intellectual awakening in the West, despite being frequently overlooked in mainstream historical narratives. This study also emphasizes the need for a fair and inclusive historical reconstruction to fully understand the interconnectedness of Islamic and Western civilizations.